EFFECT OF CARBON DI SULPHIDE ON GERMINATION OF RABI CROP OF NAGDA TOWN - Kushwaha, Archana (International Journal of Research -GRANTHAALAYAH, 2015)
Carbon disulfide is a colorless volatile liquid with the formula CS2. The compound is used frequently as a building block in organic chemistry as well as an industrial and chemical non-polar solvent It is widely used in the synthesis of organosulfur compounds and is commonly used in the production of the soft fabric viscose. Carbon disulfide evaporates rapidly when released to the environment. Carbon disulfide does not stay dissolved in water very long, and it also moves quickly through soils. Soil pH directly affects the life and growth of plants because it affects the availability of all plant nutrients. Between pH 6.0 to 6.5 most plant nutrients are in their most available state. In present study the rate of germination of rabi crop was monitored. Black cotton soil from different areas of Nagda town was taken for germination of sample seeds .The study was focused on different field of Nagda. It was found that the field of Nagda town was not appropriate for seed germination. Rate of germination was found poor in comparison to other field.